Hot corrosion behavior of plasma sprayed 8YSZ-alumina- CNT composite coating in Na2SO4–60% V2O5 molten salt environment. Issue 17 (1st December 2018) - Thakare, J.G.; Mulik, R.S.; Mahapatra, M.M.; upadhyaya, Rohit
Abstract: Hot corrosion (HC) behavior of air plasma sprayed 8% yttria stabilized zirconia (8YSZ) -alumina (YA) composite thermal barrier coating has been evaluated in the present work. Three variants of YA coatings were produced, two by reinforcing 1%, 3% multiwall carbon nanotube (MCNT) and one coating was obtained without any MCNT reinforcement. The creep strength enhanced ferritic P91 steel was used as substrate material for coating. Na2 SO4 and V2 O5 salts mixed in 2:3 ratio was applied to the coating and subjected to 800 °C for 120 h in an electric furnace. The microstructure and phase characterization of the coating was carried out before and after HC using scanning electron microscope (SEM) and X-ray diffraction (XRD) respectively. Energy dispersive spectroscopy (EDS) integrated with the SEM was used for elemental analysis of the coating. The investigation reveals improved isothermal HC behavior of 1% MCNT reinforced coating. The dominating effect of the HC was recognized as depletion of yttria leading to destabilization of 8YSZ. The formation of YVO4 was the corrosion product containing the depleted Y2 O3 of YSZ. The 1% and 3% MCNT reinforced coating exhibited monoclinic phase percentage of around 9% and 34% respectively. Nanoindentation was carried out along the cross-section before and after the isothermal HC. The Youngs modulus after HC increased by 46%, 42%, 12.5% and 38% for 8Y, 8YA, 8YA1C and 8YA3C coating, respectively. Weibull modulus of Youngs modulus of bond coats was used to identify the efficiency of top coat in retarding the infiltration of molten salt. The bond coat of 8YA1C coating exhibited lowest modulus value (m = 8.55) indicated non-uniform infiltration of detrimental species. The 1% MCNT reinforced thermal barrier coating (TBC) system was more resistant to degradation than the conventional 8YSZ and YA composite coatings.